2003
DOI: 10.1007/bf03345264
|View full text |Cite
|
Sign up to set email alerts
|

Derangement of glucose metabolism in hyperparathyroidism

Abstract: The derangement of glucose metabolism is found frequently in all forms of hyperparathyroidism. Both in primary (PHPT) and secondary hyperparathyroidism (SHPT) PTH excess is thought to be involved in deteriorating insulin sensitivity and secretion though their different clinical and pathophysiological conditions. In PHPT these abnormalities are related to a high frequency of Type 2 diabetes mellitus and also impaired glucose tolerance according to recent clinical studies, without differences between symptomatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 57 publications
3
51
0
6
Order By: Relevance
“…The relationship between vitamin D, Ca and insulin was elucidated in 1967, when Milner and Hales [17] showed that, in animals, Ca and magnesium (tightly regulated by the VTD system) were essential for insulin secretion. Also, having an inadequate VTD status may play a role in insulin resistance [18][19][20][21]: indeed, VTD has a direct effect on insulin action, as it stimulates the expression of the insulin receptor and, thus, enhances responsiveness for glucose transport [22]. Vitamin D also has indirect (Ca-mediated) effects on insulin action: Ca is tightly regulated, and intracellular Ca 2+ concentrations must be kept within an extremely narrow range for the optimal action of insulin on different insulin-responsive tissues, such as skeletal muscle and fat tissue [23][24][25].…”
Section: Association Of Vitamin D and Type 2 Diabetes Mellitus: In Vimentioning
confidence: 99%
“…The relationship between vitamin D, Ca and insulin was elucidated in 1967, when Milner and Hales [17] showed that, in animals, Ca and magnesium (tightly regulated by the VTD system) were essential for insulin secretion. Also, having an inadequate VTD status may play a role in insulin resistance [18][19][20][21]: indeed, VTD has a direct effect on insulin action, as it stimulates the expression of the insulin receptor and, thus, enhances responsiveness for glucose transport [22]. Vitamin D also has indirect (Ca-mediated) effects on insulin action: Ca is tightly regulated, and intracellular Ca 2+ concentrations must be kept within an extremely narrow range for the optimal action of insulin on different insulin-responsive tissues, such as skeletal muscle and fat tissue [23][24][25].…”
Section: Association Of Vitamin D and Type 2 Diabetes Mellitus: In Vimentioning
confidence: 99%
“…A higher prevalence of DM has been detected in patients with pHPT. 10,13,15 Reports on the effect of parathyroidectomy (PTX) on DM in patients with pHPT are contradictory. Some studies have shown a beneficial effect, 15,32 one no benefit 33 and one partial improvement.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 The ensuing hypercalcemia can lead to interstitial calcification in the allograft with graft dysfunction 5,6 and soft tissue calcification. 7,8 Primary hyperparathyroidism (pHPT) 9,10 and sHPT 11,12 are both associated with abnormalities in glucose metabolism, such as glucose intolerance and insufficient insulin release. Furthermore, a higher prevalence of diabetes mellitus (DM) has been reported in patients with pHPT.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown through different studies that parathormone excess can reduce glucose tolerance 16 and induce inflammatory cytokines like IL-6 and its soluble receptor (IL-6sR) 17 and thereby may contribute to development and progression of diabetic retinopathy.…”
Section: Introductionmentioning
confidence: 99%